Circular Strategy Through Heat Treatment of Recycled Piston Rings for the Sustainability of the Automotive Economy - Abdillah, Fuad; Fatra, Fahmi (Indonesian Journal Publisher, 2025)
This study investigates the enhancement of mechanical performance in recycled piston rings through strategic heat treatment. The research focuses on optimizing heat treatment parameters—including austenitizing temperatures (800°C, 850°C, and 900°C), holding times (1, 2, and 3 hours), and cooling media (water, oil, and air)—to restore the hardness of used piston rings to levels comparable to new ones. Experimental methods were employed to evaluate the effects of these variables on material hardness. Results show that a holding time of three hours significantly improved hardness, with the highest achieved value reaching 38.66 HRC—nearly matching that of new piston rings (39.94 HRC). These findings demonstrate that properly controlled heat treatment can effectively rejuvenate recycled piston rings, offering a viable pathway to improve resource efficiency and reduce metal waste in the automotive industry